1995
DOI: 10.1002/jmri.1880050210
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‐enhanced MR imaging of intrahepatic cholangiocarcinoma: Pathologic correlation study

Abstract: The authors describe the enhanced magnetic resonance (MR) imaging appearance of intrahepatic cholangiocarcinoma. The MR images of eight patients with intrahepatic cholangiocarcinoma who underwent MR examination within 3 weeks before partial hepatectomy were retrospectively studied. The MR images, including a dynamic study, were compared directly with pathologic and histologic findings. The peripheral region of the medullary subtype of cholangiocarcinoma, with many tumor cells, showed greater enhancement relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
38
0
4

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(47 citation statements)
references
References 8 publications
5
38
0
4
Order By: Relevance
“…Zhang et al [8] reported that early marked enhancement of the whole tumor on early-phase CT and MRI images was shown in 2 of 20 patients with peripheral ICC, and numerous tumor cells with a moderate amount of fibrosis were seen in such tumors with early marked enhancement. Thus, the correlation of hypervascular ICC and numerous tumor cells with scant interstitial fibrous tissues have been previously reported [14,15]. Furthermore, some cases of CoCC, which is categorized as a subtype of ICC, with marked enhancement within the tumor on arterial-phase CT and MRI, have been reported [21,22].…”
Section: Discussionmentioning
confidence: 88%
“…Zhang et al [8] reported that early marked enhancement of the whole tumor on early-phase CT and MRI images was shown in 2 of 20 patients with peripheral ICC, and numerous tumor cells with a moderate amount of fibrosis were seen in such tumors with early marked enhancement. Thus, the correlation of hypervascular ICC and numerous tumor cells with scant interstitial fibrous tissues have been previously reported [14,15]. Furthermore, some cases of CoCC, which is categorized as a subtype of ICC, with marked enhancement within the tumor on arterial-phase CT and MRI, have been reported [21,22].…”
Section: Discussionmentioning
confidence: 88%
“…In our series, 38% (10/26) of CCA tumors in 86% (6/7) of CCA patients demonstrated the homogeneous hyperintense pattern of delayed gadolinium retention felt to be characteristic of CCA [9,11]. This pattern of hyperintense signal intensity on delayed postcontrast images was not specific for CCA among malignant tumors, for 6% (7/121) of HCC tumors in 15% (7/47) of HCC patients, 6% (1/17) of colon carcinoma metastases in 14% (1/7) of colon carcinoma patients, and 24% (18/ 73) of other tumors (including EHE, NE tumors, metastatic breast carcinoma, and metastatic adenocarcinoma of unknown origin) in 38% (6/16) of patients with these other tumors also had homogeneous hyperintense signal intensity from delayed gadolinium retention.…”
Section: Discussionmentioning
confidence: 87%
“…In other CT and MR reports, CCAs have been described to have either heterogeneous or homogeneous delayed retention of contrast [5][6][7][8][9][10][11]. Differences between fibrous tumors showing delayed homogeneous versus heterogeneous retention of contrast remain uncertain.…”
Section: Discussionmentioning
confidence: 94%
“…4 In fact, a small number of ICC tumors with early enhancement and delayed washout pattern on MR imaging have already been reported, although these are very rare. 4,5 Areas of an ICC with early enhancement and rapid washout pattern seem to indicate active growth. 3 Again, I feel that a final conclusion for the specificity of delayed MR imaging requires further large-scale studies in patients with cirrhosis.…”
mentioning
confidence: 99%